Race between virus and inflammasomes: inhibition or escape, intervention and therapy - Wu, Nijin; Zheng, Chunzhi; Xu, Jiarui; Ma, Shujun; Jia, Huimin; Yan, Meizhu; An, Fuxiang; Zhou, Yi; Qi, Jianni; Bian, Hongjun (Frontiers in Cellular and Infection Microbiology, 2023)
The inflammasome is a multiprotein complex that further regulates cell pyroptosis and inflammation by activating caspase-1. The assembly and activation of inflammasome are associated with a variety of diseases. Accumulative studies have shown that inflammasome is a key modulator of the host’s defense response to viral infection. Indeed, it has been established that activation of inflammasome occurs during viral infection. At the same time, the host has evolved a variety of corresponding mechanisms to inhibit unnecessary inflammasome activation. Therefore, here, we review and summarize the latest research progress on the interaction between inflammosomes and viruses, highlight the assembly and activation of inflammosome in related cells after viral infection, as well as the corresponding molecular regulatory mechanisms, and elucidate the effects of this activation on virus immune escape and host innate and adaptive immune defenses. Finally, we also discuss the potential therapeutic strategies to prevent and/or ameliorate viral infection-related diseases via targeting inflammasomes and its products.